Long-term safety of biologics in the treatment of psoriasis - Panchal MR; Coope H; McKenna DJ; Alexandroff AB (Dove Medical Press, 2013)
Manisha R Panchal,1 Helen Coope,2 D John McKenna,3 Anton B Alexandroff31Department of Dermatology, Sherwood Forest Hospitals, Kingsmill Hospital, Nottinghamshire, 2Novartis Pharmaceuticals UK Ltd, West Sussex, 3Department of Dermatology, University Hospitals of Leicester, Leicester Royal Infirmary, Leicester, UKAbstract: Biologics are novel and important agents in the treatment of severe psoriasis. These agents block specific molecular steps in the inflammatory cascade, thereby reducing activation and proliferation of keratinocytes. Prescreening for biologic agents and careful monitoring of patients is important. There are four biologics currently licensed and used in the treatment of psoriasis in the European Union. This is an evidence-based review examining clinical trials and focusing on the long-term safety data for four biologic agents. Current British Association of Dermatology guidance for the use of biologics in psoriasis and guidelines on the management of psoriasis from the National Institute for Health and Clinical Excellence have been used. Advances on safety information since 2009 in clinical trials are reviewed. The results show that overall there is no statistical significance in the incidence of adverse effects of biologics versus placebo. However, there are serious adverse effects that are reported for biologics that need to be assessed for and addressed promptly. Results of studies discussing major adverse cardiovascular events are also reviewed.Keywords: psoriasis, biologic agents, safety profile, major cardiovascular events